Understanding Pathobiology of Epizootic Ulcerative Syndrome (EUS) Causing Aspergillus fumigatus and Its Immunological Response in Freshwater Fish of Channa striatus - Podeti Koteshwar Rao (Contemporary Research and Perspectives in Biological Science Vol. 2, 2024)
The present study highlights the pathology and pathobiology of Epizootic Ulcerative Syndrome (EUS) caused by Aspergillus fumigatus and its immunological response in freshwater fish of the species Channa striatus. Understanding the role of the environment and its impact on the growth of A. fumigatus is essential for improving disease management systems against EUS infection. Aspergillus fumigatus, an oomycete fungus, is frequently recognized as a causative agent of EUS, a seasonal and epidemic pathogen of significant concern in cultured fish in both freshwater and estuarine environments. In Channa striatus species, EUS is a complex infectious condition that results in necrotic ulcerative lesions and granulomatous reactions, contributing to significant mortality. This syndrome has caused the death of approximately 92 fish species recorded in the wild and in commercial aquaculture systems worldwide. Various environmental and biological factors contribute to the growth and establishment of A. fumigatus, which further invites secondary pathogens into the lesions, exacerbating the fungal infection. Proper identification methods for A. fumigatus include PCR detection and light microscopy. A deeper understanding of the infection process is necessary to discover effective treatments for controlling the disease. Research on fungal infection in Channa striatus reveals patterns of the fish’s immune response to A. fumigatus, which is crucial for developing vaccines and targeted treatments to prevent the disease and maintain EUS-free aquaculture systems. Discussions in this area include immune mechanisms triggered by infection, interactions between A. fumigatus and the immune system of the host species, the various clinical states of A. fumigatus, and alternative treatment modalities.